Theoretical and Experimental Study of Operation of the Tank Equipment for Ultrasonic Purification of the Internal Combustion Engine Exhaust Gases - Adil Kadyrov; Aleksandr Ganyukov; Igor Pak; Bahtiyar Suleyev; Kyrmyzy Balabekova (Communications - Scientific letters of the University of Zilina, 2021)
The article presents results of scientific and experimental studies of the authors on operation of the tank equipment for ultrasonic purification of exhaust gases of internal combustion engines designed to reduce environmental pollution.The scheme of the experimental device implementing the principle of the tank equipment operation for ultrasonic cleaning of the motor vehicles exhaust gases is presented; the obtained experimental data of ultrasonic coagulation processes were processed and analyzed. Empirical relationships of the coagulation coefficient and its rate of change are derived from experimental data.